Sources of resistance to Pseudomonas syringae pv. phaseolicola races in Phaseolus vulgaris - Taylor, JD; Teverson, D.M.; Davis, J.H.C. (Wiley, 1996)
One thousand and forty-eight Phaseolus bean accessions were evaluated for resistance to six races of Pseudomonas syringae pv. phaseolicola. The accessions originated from regions of the Americas and Africa where the disease is important and included wild type accessions and some known resistance sources. Resistance, graded on a five-point scale, was of two types: qualitative, which was shown to be race-specific, and quantitative. Race specific resistance genes (R-genes) were detected in 49.4% of accessions with the following gene frequencies: R1 (10.3%), R2 (0.3%), R3 (25.0%), R4 (35.0%) and R5 (0.2%).